How people perceive malicious comments differently: factors influencing the perception of maliciousness in online news comments - Lee, Saerom; Baek, Hyunmi; Kim, Seongcheol (Frontiers in Psychology, 2023)
This study proposes a comprehensive model to investigate the factors that influence the perceived maliciousness of online news comments. The study specifically examines individual factors, including demographic characteristics (e.g., gender and age), personality traits (e.g., empathy and attitudes toward online news comments), and reading-related factors (e.g., the amount of news comment reading). Contextual factors such as issue involvement, perceived peer behavior, and the presence of malicious comments in news articles are also considered. The results suggest that most of the proposed variables have a significant impact on the perceived maliciousness of online news comments, except for morality and issue involvement. The findings have important theoretical implications for research on malicious online news comments and provide practical guidelines for online news platforms on how to reduce malicious comments by visualizing them alongside other news comments.